Estimasi Kapasitas Daya Tampung Landfill dan Umur Pakai TPA Gili Trawangan: Estimasi Kapasitas Daya Tampung Landfill dan Umur Pakai TPA Gili Trawangan - Selvia, Siska Ita; Iemaniiah, Zuhdiyah Matiienatul; Dewi, Rika Andriati Sukma; Maftuh, Miftahul; Akbar, Sandi; Siddiqirly, Muhammad (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2023)
This research aims to calculate the estimated landfill capacity and the remaining operational life of the landfill on Gili Trawangan. The condition of the pile of rubbish in the landfill area, which is becoming increasingly mountainous day by day without any compaction and stockpiling process, has resulted in the operational lifespan being reduced over time. Limited land on small islands such as Gili Trawangan is a significant obstacle that must be considered with more intensive waste reduction efforts and integrated waste management. By knowing the remaining operational life based on the projected waste volume for the next 20 years and also the height of the waste pile at the Gili Trawangan TPA, it is hoped that it will be an early warning, especially for the Regional Government, the local community of Gili Trawangan and stakeholders related to waste management to take quick steps in managing the waste pile. The method used in this research is a descriptive, evaluative method starting with a geometric equation approach to calculate projections of waste generation, the carrying capacity of the landfill on Gili Trawangan and estimates of the remaining operational life. The results of this research are that the remaining operational life of the landfill is 3 years. It represents an alarming condition because it will contribute to the increasing vulnerability of small islands, especially Gili Trawangan, especially the decline in environmental conditions.